(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2019)
Motivation: The emergence of additive manufacturing technologies offers an opportunity to design sophisticated 3D structures. Among all the different technologies, the stereolithography seems to be the most promising approach for biomedical applications and especially in tissue engineering. Indeed, stereolithography is known to generate complex geometries with high resolution and quickness. In terms of materials used for tissue engineering scaffold, hydrogels are by far to be the most attractive materials due to the close properties with the body tissues. From this perspective, some resins based on gelatin have already been reported to provide favorable cellular adhesion, but display ineffective mechanical properties. That is why, the demand to produce new multifunctional resins answering to the mechanical and biological requests becomes crucial. Materials and Methods: In this aim, we investigated a hybrid polymer based on gelatin (for its biological properties) and poly(trimethylene carbonate) (PTMC) (for its mechanical properties). Two synthetic ways were studied: PTMC grafts onto the gelatin (grafting onto) and the polymerization of trimethylene carbonate (TMC) from the gelatin (grafting from). The goal of these complementary ways is to tune polyvalent materials from hydrogel to elastomer only by adjusting the composition of gelatin and PTMC. Results and Discussion: These two ways of synthesis have already been performed and the resulting polymeric materials were fully characterized. Mechanical and biological properties have been attempted. The feedback of these trials would permit to improve the upstream material elaboration. Finally, these hybrid polymers are tested by stereolithography to shape 3D porous structures. Conclusion: This project will allow to customize plethora of scaffolds related to the polymer composition and the architecture by stereolithography.